The Development of Enterprise Resource Planning (ERP) using the Rapid Application Development (RAD) Method for the Garment Industry in Indonesia - Muhammad Raihan Gifari Qowindra; Jansen Wiratama (Universitas Islam Raden Rahmat, Malang, 2023)
One of the Indonesian companies engaged in the Garment Industry is PT Mardohar Catur Tunggal Gaya. This company focuses on manufacturing garments, safety clothing, and industrial work clothing. Based on an analysis of the processes running in this company, business processes still need assistance regarding report integration. Several approaches to solving business needs are carried out by observing, interviewing, and reviewing the literature to address these obstacles. The results of interviews with companies that were later observed revealed that PT Mardohar Catur Tunggal Gaya needed to implement a system to optimize its business processes. Furthermore, from the literature review results, it was found that the right system to overcome these obstacles was Enterprise Resource Planning (ERP). The ERP system used is Oddo, and its development will be carried out using the Rapid Application Development (RAD) method. The result of this study is the modified Odoo ERP system with the addition of several modules according to business needs. The results of functional testing using the User Acceptance Test (UAT) testing method illustrate that the developed ERP system follows user needs and is feasible to implement.